Comportamiento físico, químico y clínico de los materiales MTA y biodentine en el recubrimiento pulpar directo. revisión narrativa. - Chalarca Torres, Natalia Andrea; Díaz Pereira, Heidy Daniela; Gómez Gutiérrez, Judith Andrea (Universidad Antonio Nariño, 2022)
The clinical success rate in pulp capping depends on the materials used as a substitute for damaged dentin. For many years calcium hydroxide was t appearance in 1995 of mineral trioxide aggregate he material generally used, until the MTA, and recently of compounds such as Biodentine. There are several studies comparing the properties and success rate, which are addressed in this work